Prekinjena kontinuiteta poselitve mariborskih stanovanjskih hiš leta 1945 - Ferlež, Jerneja (Studia Historica Slovenica, 2016)
In this piece the author describes the characteristics of a changing housing fund in the period of continual transit and confronts them with the circumstances of turning point periods. She describes the conditions in Maribor after the First World War and especially in the year 1945, when the continual transition had been drastically interrupted. She describes a bombed out city, post-war confiscations, the partial emptying of the city and residential houses, and the circumstances of new settlement in the empty houses in the months following the end of the world war. She describes the concrete examples of two such houses - a craft house in the old part of the city and a villa in the villa quarter. She realises that the end of the Second World War was not only a turning point but also in a long term changed the ways in which people transit in habitation environments.
Keywords: 1945; druga svetovna vojna; Maribor; stanovanja; stanovanjske zgradbe; svetovna vojna 1939-1945